Моделювання багатокритеріальної задачі оптимізації вибору методики побудови СУІБ методами Томаса Сааті - Фукс, М. А. (ХНУРЕ, 2024)
The aim of the work is to analyze the purpose of the multi-criteria optimization, which is gaining much more popularity during the last decades. Thomas L. Saaty took part in the development of two methods to solve this type of problem, namely the Analytic Network Process and the Analytic Hierarchy Process. When choosing a methodology for building an ISMS, a CISO seeks to determine the best of the available alternatives. This task has been modeled using both of the abovementioned methods taking into account the presence of potential internal relationships between the described criteria.
Keywords: побудова СУІБ методами Томаса Сааті; моделювання багатокритеріальної задачі